2004
DOI: 10.1111/j.1523-1755.2004.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro-MRI methods to detect renal cysts in mice

Abstract: Micro-MRI with 3D-FIESTA can depict cyst formation in the diseased kidneys of living mice without injection of contrast agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…It is important that the dendrimer-contrast agent is used by other investigators with different models of ARF (and chronic renal failure [23]) both to confirm our findings and to produce further insights into the pathophysiology of renal injury. Obviously, the next step is to use this contrast agent in humans – both with normal renal function and with renal injury.…”
Section: Introductionsupporting
confidence: 50%
“…It is important that the dendrimer-contrast agent is used by other investigators with different models of ARF (and chronic renal failure [23]) both to confirm our findings and to produce further insights into the pathophysiology of renal injury. Obviously, the next step is to use this contrast agent in humans – both with normal renal function and with renal injury.…”
Section: Introductionsupporting
confidence: 50%
“…Recent studies have illustrated the potential of MR to elucidate the development of renal cysts in the course of ADPKD in clinical studies [14,15] and also in animal models of cystic diseases [4,12,13,18]. Recently, Wallace et al showed that in vivo measurements of kidney volume using a dedicated animal scanner can accurately monitor the increase of renal volume in disease models [18].…”
Section: Discussionmentioning
confidence: 98%
“…MRI has already proven to be a reliable method to measure renal volumetric indices in preclinical [4,12,13] and clinical studies [14][15][16][17]. Therefore, MRI-based volume measurements can be used as a reliable medium to detect the progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Using the renal suction method, transgene expression was observed to a depth of at least 700 lm (Figure 3(A)). The total thickness of the renal cortex in mice is reported to be about 1 mm from the surface (Zhai et al, 2003;Kobayashi et al, 2004). The depth of transgene expression using the renal suction method could be sufficient to deliver pDNA to the deep cortex of the kidney.…”
Section: Discussionmentioning
confidence: 99%